2018
DOI: 10.1155/2018/6084541
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risky Drinking Patterns among College Students from Selected Countries of the Carpathian Euroregion

Abstract: Reduction of excessive alcohol consumption still remains a significant challenge to the actions in the scope of public health of European citizens. The aim of this study is to present the prevalence of alcohol consumption and to estimate the occurrence of risky drinking among college students from the Polish, Slovak, Romanian, and Ukrainian parts of the Carpathian Euroregion, taking social contexts into account. The consumption of alcohol was estimated on the basis of the respondents' statements regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
5
18
1
10
Order By: Relevance
“…This results are quite predictible and corelated with the results from scientific literaature which proved that worldwide the use of alcohol is much frequent at men comparing with women [19][20][21] .…”
Section: Resultssupporting
confidence: 81%
“…This results are quite predictible and corelated with the results from scientific literaature which proved that worldwide the use of alcohol is much frequent at men comparing with women [19][20][21] .…”
Section: Resultssupporting
confidence: 81%
“…Starting university and living away from home has also been associated with low consumption of fruit and vegetables among male Polish students [9]. Moreover, while studying at university, male students have shown to engage more often than girls in addictive behaviours, such as excess alcohol drinking, smoking, and the use of stimulants, e.g., to enhance mental performance and cope with stress [10,11]. Poor coping strategies, which are reflected in addictive behaviours, can be also triggered by commencing first employment, which is often a source of stress for a young person.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Across the world, it has been reported that university students' alcohol consumption is higher than their non-university peers 3,4 Alcohol misuse was also reported as a strong predictor of students' mental health in which, it was attributable to increased depressive symptoms and attempted suicide. 5,6 Tobacco and alcohol use were in the 2nd and 6th place in a 2013 ranking of the top 25 leading health risk factors in the world, respectively. 6,7 More than 27 million, which is 0.6% of the world adult population currently believed to have alcohol and other drugs such as Khat (amphetamine-like local stimulant abused drug) and tobacco-related health problems.…”
Section: Introductionmentioning
confidence: 99%